Efforts to Increase the Volume of Breast Milk Through Analysis of the Nutrients of Banana Blossoms and Papaya Leaves In Order to Increase the Coverage of Exclusive Breastfeeding As An Effort to Prevent Stunting - Marniati Marniati; Itza Mulyani; Arfah Husna; Enda Silvia Putri; Adelina Irmayani Lubis; Afwa Hayuningtyas; Suci Eka Putri; Safrida Safrida; Wardah Iskandar (International Conference on Multidisciplinary Research, 2022)
Mother's milk is the main source of nutrition for babies who are not yet able to consume solid food. Formation of breast milk is influenced by protein, vitamins, fat, water, carbohydrates, fiber and other nutrients. Problem in this study was that the mother did not give breast milk to her baby because the volume of breast milk was small, the mother did not know what foods could increase the volume of breast milk at a relatively low cost. Purpose of this study was to analyze the nutritional value of local foods such as banana blossom and papaya leaves to what extent they are able to increase the volume of breast milk in breastfeeding mothers.Research method uses pre-experimental tests (non-design) and socialization. in the Panton Reu sub-district, West Aceh Regency with a population of 44 breastfeeding mothers, a total sample of 44 respondents who met the inclusion and exclusion criteria. Results after conducting research, where the high levels of nutrients contained in the heart of bananas and papaya leaves, these nutrients are related to the formation of breast milk volume. Conclusion of the results of the analysis of nutrients, the banana flower and papaya leaves can be consumed by breastfeeding mothers because of the high levels of nutrients contained therein. According to the analysis of nutrients, banana blossom and papaya leaves need to be used as a mainstay for the family, and further research needs to be done and this research can be used as a reference source. Keywords: Breastfeeding mother, breast milk volume, nutrients, banana blossom, papaya leaf